Primary Orbital Marginal Zone B-cell Lymphoma: A Rare Case Report - Ranjana Giri; Nageswar Sahu; Prita Pradhan; Dhanasree Surendran Vellikal; Goutami Das Nayak (Journal of Clinical and Diagnostic Research)
Orbital Lymphomas (OL) account for 1 to 2% of Non Hodgkin Lymphomas (NHLs) and 2 to 11% of all orbital tumours. The most common primary OL is low-grade marginal zone B-cell lymphoma. This is a case of primary orbital NHL mimicking an orbital pseudotumour. A 67-year-old male presented with a swollen right eye associated with lacrimation for two months. On examination, there was right eye proptosis. Thyroid, liver and renal function tests were within normal limits. Contrast Enhanced Computed Tomography (CECT) revealed a homogenously enhancing intraconal mass measuring 4.1×3.2×2.8 cm, with features favouring a benign aetiology. Cytosmears revealed features suggestive of inflammatory pseudotumour of the orbit. Histopathological findings suggested low-grade NHL. Immunohistochemistry (IHC) showed positivity for CD20, CD79a, PAX5, and Bcl2, and negativity for CD3, CD5, CD10, CD23, Bcl6, and Cyclin-D1. Hence, a final diagnosis of marginal zone B-cell lymphoma was rendered. Detailed clinical and radiological evaluations did not reveal lymphadenopathy anywhere else or any other focus of tumour, indicating the primary origin of this tumour in the orbit. Primary NHL of the orbit is rare. It can occur in the orbit without any systemic features. It must be diagnosed early and can be treated with surgery and chemotherapy.